Determination of Trapezoidal Sharp-Crested Weir Coefficient - Sri-Amporn, Winai; Kiemkratok, Chakri; Saenwong, Thanakorn; Ratanaprapan, Tawatchai (Engineering and Applied Science Research, 2013)
The determination of various side slope angles trapezoidal sharp-crested weir coefficient is presented. Nine weir plates were made from braze plate with a trapezoidal shape cutting, at various side slope angles. The angles are ranging from about 5 to 45 degree. A weir plate was installed to a flume, and the experiment was carried out in a laboratory, The discharge through a weir plate, and the water level above weir crest (head), were measured. The discharge was determined by measuring volume of water per unit time. The results of this study provided the weir coefficients, Furthermore, the relationships between discharge and head, weir coefficient and side slope angle, and weir coefficient and discharge are increased as the increasing of the side slope angle. Beside, the weir coefficient is decreased as increasing of head.